In Vitro Antibacterial Activity of Eco Enzyme of Eucalyptus (Melaleuca leucadendra) against Escherichia coli - Muhammad Aafi Baharuddin Attamimi; Wiwin Retnowati; Ummi Maimunah; Eko Budi Koendhori (Universitas Airlangga, Surabaya, Indonesia, 2025)
Highlights It has been proven that the eucalyptus eco-enzyme from Lamongan does not exhibit strong enough antibacterial activity against E. coli at any concentration. The eucalyptus eco-enzyme method is less effective at extracting active compounds compared to distillation processing. Abstract Background: Eucalyptus (Melaleuca leucadendra) is known to have antimicrobial potential due to its bioactive terpenoid compounds, including 1,8-cineole. This compound has the potential to inhibit the growth of Escherichia coli, a bacterium responsible for various infectious diseases. The eco-enzyme method, which utilizes fermentation, is simple to perform and does not require complex materials. Objective: This study aimed to assess the antibacterial activity of eucalyptus eco-enzyme against Escherichia coli. Material and Method: The M. leucadendra used in this study was sourced from Candisari Village, Lamongan, Indonesia and E. coli was obtained from laboratory isolates. Antibacterial activity was measured by observing the zone of inhibition in the well diffusion test on Muller-Hinton agar, with chloramphenicol as the positive control and distilled water as the negative control. The incubation period was 24 hours at 36°C. Result: The inhibition zone around the positive control was 25.94±1.1 mm. No inhibition zone (0 mm) was observed around the negative control or the eucalyptus eco-enzyme solution at concentrations ranging from 10% to 100%. However, a clearer zone was observed around the eco-enzyme well. The inability of the eco-enzyme to inhibit the growth of E. coli may be attributed to several factors, including the ingredients, processing method, acidity level, and bacterial resistance. Conclusion: The eucalyptus eco-enzyme did not exhibit sufficient antibacterial activity against E. coli at any of the tested concentrations.